Renormalization: The observable-state model. II - Ardenghi, Juan Sebastian (2012)
The purpose of this work is to rewrite the generating functional of 4 theory for the n=0 and n=4 correlation functions as the inner product of a state with an observable, as we did in a previous work, for the two-points correlation function. The observables are defined through the external sources and the states are defined through the correlation function itself. In this sense, the divergences of Quantum Field Theory (QFT) appear in the reduced state by taking the partial trace of the state with respect to the internal vertices that appear in the perturbation expansion. From this viewpoint, the renormalization can be substituted by applying a projector on the internal quantum state. The advantage of this new insight is that we can obtain finite contributions to the correlation functions without introducing counterterms in the Lagrangian or by manipulating complex divergent quantities. © 2012 American Physical Society.